If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + 14k = k Solving -13 + 14k = k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-1k' to each side of the equation. -13 + 14k + -1k = k + -1k Combine like terms: 14k + -1k = 13k -13 + 13k = k + -1k Combine like terms: k + -1k = 0 -13 + 13k = 0 Add '13' to each side of the equation. -13 + 13 + 13k = 0 + 13 Combine like terms: -13 + 13 = 0 0 + 13k = 0 + 13 13k = 0 + 13 Combine like terms: 0 + 13 = 13 13k = 13 Divide each side by '13'. k = 1 Simplifying k = 1
| 117-3x=15x+19 | | -5x+2[-4x+3]=110 | | 4w+3=(7w-6)(7w-6) | | 12=7c-9 | | 6x^2-47x-46=0 | | 7x+7[x-5]=-147 | | -5(1-5x)+5(-8x-2)=-4x-8x+3 | | 13y+5=5y-5 | | 2(x-4)=4(x-2) | | X-(-2)=6 | | 5(x+3)=3(2x-1) | | 1a+2=(-9) | | -4x-5[-x+10]=-43 | | 6x-8(x+3)=-14 | | 8x+7x-6x=18 | | i=400*0.0013*2 | | -6x+4[-2x+8]=130 | | x^2+39x+47=0 | | -2+8=5-(10p+4) | | i=400*0.13*2 | | 2x+6[-5x-15]=190 | | 4-3x+8=5x-4 | | 70x^2-53x+9=0 | | 2(x+4)=x-7 | | 26x-14=3 | | -10+3m=2(4m+-5) | | X+50=210 | | 7x+6[-x-17]=-109 | | x+x+(x-45)+(x-45)+(x-45)=540 | | x=28.75+0.25y | | 2(x-1)+x=4+5 | | x=320+.2x |